Between Integrity and Digital Crime: An Analysis of Judges' Considerations in the Case of Electronic Document Forgery for the Selection of Candidates for State Civil Apparatus - Limantara, Benny Karya; Andriyanto, Andriyanto (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: In every joint of modern life, documents play a vital role as a means of evidence, identification, legitimacy, and a means of transaction. In the midst of an increasingly rapid wave of digital transformation, the modus operandi of document forgery has evolved.Purposes of the Research: Analyzing the criminal law regulations against the falsification of electronic documents in the selection of State Civil Apparatus Candidates (CASN), with a case study of Decision Number 512/Pid.Sus/2024/PN Tjk.Methods of the Research: Using a normative-empirical approach, primary data from interviews with investigators from the Lampung Regional Police, the prosecutor of the Bandar Lampung District Attorney's Office, and the Judge of the Tanjung Karang District Court were combined with secondary data from a literature study of laws and regulations, court decisions, and criminal law literature.Results Main Findings of the Research: The panel of judges in its decision proved the defendant's guilt through five valid evidence (witness statements, experts, letters, instructions, defendant's statements) that were correlated with each other, fulfilling Article 183 of the Criminal Code. Judicial independence is reflected in the penalty of 1 year and 6 months plus an IDR fine. 30 million, lighter than the prosecutor's demand for 4 years who balanced legal firmness with proportionality. The value of integrity is realized through the recognition of violations that maintain the meritocracy of the State Civil Apparatus Candidate, while substantive justice arises from the moderation of sanctions that take into account the context of the case and the character of the defendant. The research recommends improving people's digital literacy, cyber forensic competence of law enforcement officials, and a holistic approach of judges in handling electronic evidence. This study contributes to the discourse of criminal law in the digital era and strengthening bureaucratic integrity.